The Impact COVID-19 School Closures on Educational Inequalities - Mahmut Özer; Hayri Eren Suna; Petek Aşkar; Zafer Çelik (İnsan & Toplum)
During the new coronavirus pandemic, schools were closed suddenly in almost every country in the world, and education services continued with the distance education solutions. However, the consequences of the school closures, maintaining education services via distance education and the deprivation of other services provided by schools have not been adequately evaluated. In this study, the effects of school closures and distance education on families and students during the Covid-19 pandemic were reviewed. Parental involvement, physical and technological possessions at home, digital literacy levels of students and parents have become the main factors that determines the efficiency of distance learning during the pandemic. As a result, there is a possibility that inequalities in education will increase more in pandemic. Inequalities in education had an important impact on the unemployment and loss of income, learning loss of students and psychological conditions, reaching healthy nutrition, need for special education, and fragile students. Although distance education was considered as an opportunity to reduce learning loss of students due to school closures during the pandemic, unfortunately it also made possible to increase the inequalities in education during the pandemic period.